Lung abscess with pneumonia after SARS-CoV-2 infection – a case report - Borys, Renata; Szeliga, Ewa; Wojtuń, Kazimierz; Kużdżał, Adrian; Sawka, Karolina (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Some patients after the SARS-CoV-2 infection may be at higher risk of consequent bacterial or fungal infections even if they have no risk factors (advanced age, obesity, metabolic diseases). A possible complication of SARS-CoV-2 infection is lung abscess with pneumonia what requires further examination and specialized treatment as well as the pulmonary rehabilitation. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. This report presents all stages of the diagnosis and treatment of lung abscess with pneumonia of male patient, aged 42 years in course of COVID-19. The article emphasizes the role of pulmonary rehabilitation in decreasing the number of postoperative pulmonary complications. Presented case report includes a description of a rehabilitation program conducted during the patient’s hospitalization. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Lung abscess is a serious disease with an often unpredictable course, complications and an uncertain prognosis. However, most patients can be treated conservatively, and the priority in treatment is antibiotic therapy and physiotherapy treatments.